Synthesis and LPG sensing properties of nano-sized cadmium oxide - Waghulade, R. B.; Patil, P. P.; Pasricha, Renu (Talanta, 2007)
This paper reports the synthesis and liquid petroleum gas (LPG) sensing properties of nano-sized cadmium oxide (CdO). The nano-sized CdO powder was successfully synthesized by using a chemical co-precipitation method using cadmium acetate and the ammonium hydroxide, as starting materials and water as a carrier. The resulting nano-sized powder was characterized by X-ray diffraction (XRD) measurements and the transmission electron microscopy (TEM). The LPG sensing properties of the synthesized nano-sized CdO were investigated at different operating temperatures and LPG concentrations. It was found that the calcination temperature and the operating temperature significantly affect the sensitivity of the nano-sized CdO powder to the LPG. The sensitivity is found to be maximum when the calcination temperature was 400 degrees C. The sensitivity to 75 ppm of LPG is maximum at an operating temperature 450 degrees C and it was found to be similar to 34 1 %. The response and recovery times were found to be nearly 3-5s and 8-10s, respectively. The synthesized nano-sized CdO powder is able to detect up to 25 ppm for LPG with reasonable sensitivity at an operating temperature 450 degrees C and it can be reliably used to monitor the concentration of LPG over the range (25-75 ppm). The experimental results of the LPG sensing studies reveal that the nano-sized CdO powder synthesized by a simple co-precipitation method is a suitable material for the fabrication of the LPG sensor. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: chemical co-precipitation; Gas sensor; LPG; nano-sized CdO

Scanning tunneling microscopic and field emission microscopic studies of nanostructured molybdenum film synthesized by electron cyclotron resonance plasma - Purohit, Vishwas S.; Bhise, Ashok B.; Dey, Shirshendu; More, Mahendra A.; Dharmadhikari, C. V.; Joag, Dilip S.; Pasricha, Renu; Bhoraskar, S. V. (Vacuum, 2008)
Cathodic sputtering is demonstrated to be effective in synthesizing thin films of molybdenum nanoparticles. An electron cyclotron resonance plasma reactor has been used as the source. The particle size distribution is found to be controllable by proper choice of the cathodic bias potential. Sizes ranging between 20 and 30 nm deposited at the optimum bias potential are found to exhibit a self assembled structure as observed by scanning tunneling microscopy. Field emission microscopic studies on these films supported on W have exhibited very stable emission current over a period of 3 h. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: ECR plasma; Field emission microscopy; Hollow cathode chemical sputtering; Mo nanoparticles; Scanning tunneling microscopy

Sheet-forming abiotic hetero foldamers - Baruah, Pranjal K.; Sreedevi, Naduthottiyil K.; Majumdar, Baisakhi; Pasricha, Renu; Poddar, Pankaj; Gonnade, Rajesh G.; Ravindranathan, Sapna; Sanjayan, Gangadhar J. (Chemical Communications, 2008)
Abiotic hetero oligomers, adopting a well-defined extended self-assembled sheet-like structure, derived from conformationally constrained aliphatic and aromatic amino acid residues repeating at regular intervals are reported.

Shape and size selective separation of gold nanoclusters by competitive complexation with octadecylamine monolayers at the air-water interface - Pasricha, Renu; Singh, Amit; Sastry, Murali (Journal of Colloid and Interface Science, 2009)
The paper presents a time-dependent study of shape-dependent preferential complexation of gold nanoparticles to the octadecyl amine (ODA) monolayers at the air-water interface. Room temperature reduction of chloroaurate ions using lemon grass leaf extract yields a Mixture of spherical and triangular nanoparticles, which were used for this study. These nanoparticles have a net negative charge on their surface due to the presence of biomolecules from plant extract and thus a strong attractive electrostatic interaction with the positively charged ODA monolayers drives the complexation process. The extent of preferential complexation of the gold nanoparticles to the ODA monolayers is a function of the charge on the particles and the relative mobility of the nanoclusters in the medium. The complexation process has been followed in real time by a host of techniques such as surface pressure-area (pi-A) isotherms, UV-vis-NIR spectroscopy and Brewster angle microscopy. The charge and mobility of the gold nanoparticles was confirmed by measurement of their electrophoretic mobility. Langmuir-Blodgett films of the nanogold-ODA composites have been characterized by UV-vis-NIR spectroscopy, Fourier transform infrared spectroscopy, and transmission electron microscopy. These measurements clearly indicate that the cluster mobility and complexation increase with decreasing cluster size. In the competitive complexation process of large and small gold particles, it was observed that some bigger gold particles were also incorporated into the amine matrix even though the cluster mobility is higher for smaller gold particles. (c) 2009 Elsevier Inc. All rights reserved.
Keywords: Competitive complexation; gold nanoparticles; Langmuir-Blodgett technique; ODA monolayer

Silver fused conducting fiber formation of Au-Ag core-shell nanoparticles mediated by ascorbic acid - Murugadoss, A.; Kar, Manoranjan; Pasricha, Renu; Chattopadhyay, Arun (Plasmonics, 2009)
In this paper, we report the spontaneous formation of fibrous structures consisting of assemblies of Au-Ag core-shell nanoparticles (NPs) from a solution consisting of Au-Ag core-shell NPs and l-ascorbic acid (AA). AA acted both as the reducing agent for the generation of NPs and also as the mediator for the formation of fibers. The process of fiber formation involved three steps-reduction of HAuCl(4) to Au NPs by AA, subsequent formation of Au-Ag core-shell NPs after addition of AgNO(3), and spontaneous formation of fibers from the mixtures in water. It took typically about 30 days to form complete fibers that are of lengths of several hundred micrometers to millimeters, although nanofibers started forming from the first day of solution preparation. The width of each of these fibers was typically about 1-4 A mu m with length of each segment of fiber bundle, on the order of 40 A mu m. Formation of fibers was also observed in absence of AgNO(3). These fibers consisted of Au NPs and polymer of AA degradation products and were not electrically conducting. Also, low concentrations of AgNO(3) produced fibers with low electrical conductivity. However, it was observed that increase in the amount of AgNO(3) leads to the formation of fibers that were electrically conducting with conductivity values in the range of metallic conductivity. Spectroscopic and electron microscopic investigations were carried out to establish the formation of fibers. The details of fiber formation mechanism under different conditions and electrical conductivities of the fibers are discussed in the article.
Keywords: Ascorbic acid; core-shell; Fiber; Gold; Nanoparticles; Silver

Synthesis of catalytically active porous platinum nanoparticles by transmetallation reaction and proposition of the mechanism - Pasricha, Renu; Bala, Tanushree; Biradar, Ankush V.; Shubhangi B. Umbarkar; Sastry, Murali (Small, 2009)
A facile method for the synthesis of porous platinum nanoparticles by transmetallation reactions between sacrificial nickel nanoparticles and chloroplatinic acid (H(2)PtCl(6)) in solution, as well as at the constrained environment of the air water interface, using a Langmuir-Blodgett instrumental setup is presented. To carry out the transmetallation at the air-water interface hydrophobized nickel nanoparticles are assembled as a monolayer on the sub phase containing platinum ions. The porous Pt nanoparticles obtained as a result of the reaction are found to act as extremely good catalysts for hydrogenation reaction. The products are well characterized by TEM, HRTEM, EDAX, and STEM. Attempts are made to postulate the plausible mechanism of this reaction to generate this kind of nanoparticle with controllable geometric shape and structure. This simple strategy has the potential to synthesize other nanomaterials of interest too.
Keywords: Catalysts; Interfaces; Nickel nanoparticles; porous platinum; Transmetallation